The Impact of Neonatal Pneumonia on Infant Health; A Review - Prasad, P. Dharani (Asian Journal of Pharmaceutics (AJP), 2024)
Neonatal pneumonia may occur in isolation or as one component of a larger infectious process. Bacteria, viruses, fungi, and parasites are all potential causes of neonatal pneumonia and may be transmitted vertically from the mother or acquired from the post-natal environment. The patient’s age at the time of disease onset may help narrow the differential diagnosis, as different pathogens are associated with congenital, early-onset, and lateonset pneumonia. Supportive care and rationally selected antimicrobial therapy are the mainstays of treatment for neonatal pneumonia. The challenges involved in microbiological testing of the lower airways may prevent definitive identification of a causative organism. In this case, secondary data must guide the selection of empiric therapy, and the response to treatment must be closely monitored.